IMPROVING TEACHING METHODS OF ENGINEERING AND COMPUTER GRAPHICS FOR STUDENTS OF THE WATER MANAGEMENT AND MELIORATION EDUCATIONAL FIELD - Khamidov Dilshod Olimjon ugli (Modern American Journals, 2025)
This article highlights modern and innovative teaching methods for the subject of Engineering and Computer Graphics for students majoring in Water Management and Melioration. The shortcomings of traditional teaching approaches are analyzed, and a method based on the use of AutoCAD software is proposed. The effectiveness of this improved methodology is substantiated through practical experiments.
Keywords: AutoCAD, engineering graphics, water management, melioration, innovative education, digital competence, drawing, project-based learning.